2022
DOI: 10.3390/ma15248884
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution and Enhanced Hot Workability of TiC/Ti-6Al-4V Composites Fabricated by Melt Hydrogenation

Abstract: Improving the hot workability and reducing the processing cost are critical steps to expanding the application of TiC/Ti-6Al-4V composites. This study employed melt hydrogenation to fabricate TiC/Ti-6Al-4V composites under a mixed atmosphere of hydrogen and argon. Experimental results indicated that hydrogen had an obvious influence on the growth and morphology of eutectic TiC particles, and the size of eutectic TiC and primary β grains was significantly increased. As a result, large-sized eutectic TiC was dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…To overcome these shortcomings, we added hydrogen to the metallurgical process, which involved smelting raw materials under an atmosphere of hydrogen/argon mixture, termed Melt Hydrogenation Technology (MHT) [ 29 ]. MHT can simultaneously complete the synthesis and hydrogenation of titanium-based materials, including titanium alloys [ 30 , 31 ], γ-TiAl alloys [ 32 , 33 ], and TMCs [ 34 , 35 , 36 , 37 ]. In the literature [ 34 ], the hot workability of (TiB + TiC)/Ti-6Al-4V composite prepared by MHT was investigated; it was found that hydrogen induced the competing of softening and hardening in the hydrogenated TMCs at different deformation temperatures and that MHT improved the motion coordination between the reinforcements and matrix during hot compression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these shortcomings, we added hydrogen to the metallurgical process, which involved smelting raw materials under an atmosphere of hydrogen/argon mixture, termed Melt Hydrogenation Technology (MHT) [ 29 ]. MHT can simultaneously complete the synthesis and hydrogenation of titanium-based materials, including titanium alloys [ 30 , 31 ], γ-TiAl alloys [ 32 , 33 ], and TMCs [ 34 , 35 , 36 , 37 ]. In the literature [ 34 ], the hot workability of (TiB + TiC)/Ti-6Al-4V composite prepared by MHT was investigated; it was found that hydrogen induced the competing of softening and hardening in the hydrogenated TMCs at different deformation temperatures and that MHT improved the motion coordination between the reinforcements and matrix during hot compression.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature [ 34 ], the hot workability of (TiB + TiC)/Ti-6Al-4V composite prepared by MHT was investigated; it was found that hydrogen induced the competing of softening and hardening in the hydrogenated TMCs at different deformation temperatures and that MHT improved the motion coordination between the reinforcements and matrix during hot compression. The literature [ 36 ] discussed the improved hot workability of TiC/Ti-6Al-4V composite prepared by MHT and found that hydrogen significantly increased the size of eutectic TiC particles and prior β grains, reduced the titanium atom bonding force, decreased the β/(α + β) transition temperature, increased the ratio of DRX, and improved the dislocation mobility. However, these studies focus more on the effects of MHT on the reinforcement or matrix and the changes produced in the matrix during hot compression, but do not design and explore the role played by their interface during hot compression deformation.…”
Section: Introductionmentioning
confidence: 99%